From Evidence to Practice: A Systematic Review and Meta-Analysis on the Effects of Supervised Exercise on Fatigue in Breast and Prostate Cancer Survivors - Cano Uceda, Arturo; García Fernández, Pablo; Peuyadé Rueda, Blanca; Cañuelo Marquez, Ana María; Solís Mencía, Cristian; Lucio Allende, Carmen; De Sousa De Sousa, Luis; Maté Muñoz, José Luis (MDPI, 2025)
Background: Breast and prostate cancer represent a significant global public health burden. Among the adverse effects of oncological treatments, fatigue is one of the most prevalent, persistent, and disabling symptoms. Therapeutic exercise has been shown to be effective for its management, with supervision identified as a key factor that may enhance adherence, safety, and intensity control. This systematic review and meta-analysis aimed to compare the effects of supervised exercise programs versus usual care on cancer-related fatigue in patients with breast or prostate cancer. Methods: A systematic search (September¿December 2024) was conducted in six databases (PubMed, Web of Science, Scopus, Cochrane, PEDro, Scielo), selecting RCTs from the past 10 years in English or Spanish. Studies compared supervised exercise with unsupervised exercise or usual care in stage I¿III breast or prostate cancer patients within five years post-treatment. Methodological quality was assessed with the PEDro scale and risk of bias with Cochrane¿s RoB 2.0. A random-effects model was used to calculate pooled effect sizes (ES, 95% CI), with heterogeneity (I2), sensitivity, subgroup, and publication bias analyses. Results: A total of 25 interventions from 19 randomized controlled trials involving over 2200 participants were included. Supervised exercise significantly reduced cancer-related fatigue compared to usual care (effect size = 0.34; 95% CI: 0.22¿0.47; p < 0.001; I2 = 56%). Sensitivity analyses supported the robustness of the findings. Subgroup analyses revealed greater effects in combined exercise programs, in men, and in patients with prostate cancer. No evidence of publication bias was observed. While 73.7% of studies were rated as having good methodological quality, the risk of bias was often unclear or high. Conclusions: Supervised therapeutic exercise programs are effective and safe for reducing fatigue in breast and prostate cancer survivors. These interventions should be incorporated into comprehensive care plans, with individualization based on patients¿ clinical and demographic characteristics. Further research is needed to identify the most effective and sustainable strategies for different patient subgroups. Keywords: therapeutic exercise; supervised; fatigue; breast cancer; prostate cancer
Keywords: therapeutic exercise; supervised; fatigue; breast cancer; prostate cancer